Digital Transformation in Micro, Small, and Medium Enterprises: Accounting Information Systems and Digital Marketing Driving Financial Performance - Burhanuddin, Fia Fauzia; Sharon, salmah; Basir, Mustika Kusuma; Syam, Asriah; Monalisa, (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2026)
This study examines the influence of Accounting Information Systems (AIS) and digital marketing on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Takalar Regency, South Sulawesi. Digital transformation has become an essential strategy for enhancing MSME competitiveness, yet many rural enterprises still face barriers in adopting financial and marketing technologies. Grounded in signaling theory, AIS and digital marketing are viewed as strategic signals that reflect transparency, accountability, and innovation within MSME operations. Using a quantitative research approach, data were collected through questionnaires distributed to 104 MSME respondents who have operated for at least two years and utilize both financial recording and digital promotion methods. Data analysis was performed using multiple linear regression with SPSS version 26. The results indicate that AIS positively and significantly affects financial performance Demonstrating that accurate and timely financial reporting improves managerial decision-making and operational efficiency. Digital marketing also shows a positive and significant effect, suggesting that effective use of online platforms enhances sales growth and customer engagement. Together, both variables explain the variation in financial performance Indicating a strong synergistic impact. This study contributes to the literature on MSME digital transformation and provides practical implications for policymakers and local governments to strengthen training, infrastructure, and technological adoption in rural business development.